Influence of ambient temperature on the production of biogas - Barrena G., Miguel (2017)
In the present investigation the influence of the ambient temperature on biogas production was determined. This relationship is necessary to establish, depending on the ambient temperature of each locality in which time and just installed a biodigester charged will be full of biogas.This tubular biodigesters PVC geomembrane, 8 and 12 m3 total volume (1.27 m diameter and 6.7 to 10 m in length) were used, with 6 and 9 m3 working volume, respectively, occupied by the mixture of cattle manure: water in the ratio 1: 5. Biodigesters were installed at seven locations of Amazonas, San Martín and La Libertad regions - Peru; different temperature and height above sea level. At each site the hydraulic retention time (HRT), in days, required for the biodigester bell ball and extra storage are full of biogas was determined.Based on the results obtained, the height above sea level and the volume of the digester does not influence the HRT; only the ambient temperature (T) directly influences the HRT, whose relationship is represented by the equation: HRT = -44.705 ln (T) + 160.394.